Phenomenon of Patriotism in Kazakhstan: Pedagogical Aspect - Ospan S. Sangilbayev3, Magripa K. Ibrayeva, Zhanbota D. Oshakbaev, (Opción, 2019)
The article is devoted to the core content components of didactic approaches to the organization of patriotic education of students in the Republic of Kazakhstan via comparative qualitative research methods. As a result, the key components of patriotic upbringing are love for Motherland, respect for its history and culture, the solidarity of the society, responsibility for the future. In conclusion, the present stage of the society and education development requires a deep rethinking of the accumulated experience and theoretical approaches to the implementation of the tasks for patriotic upbringing in the conditions of a modern university.